Perbedaan Kadar HS-CRP Menurut Indeks Massa Tubuh dan Derajat Pramenstrual Syndrome pada Remaja Usia 18 24 Tahun - Mega Ade Nugrahmi; Joserizal Serudji; Almurdi Almurdi (Universitas Batanghari Jambi, 2018)
Premenstrual syndrome occurs through the mechanism of chronic inflammation. This can be explained through the immune system which plays an important role in many aspects of women's reproductive function, including follicular recruitment, ovulation, implantation, and endometrium (Evans, 2012). The increase in CRP as a marker of inflammatory process/inflammation associated with obesity (Schulz, 2011). Body fat mass, as well as deposits of energy, it also produces adipocytokines and proinflammatory molecules such as interleukin-6 (IL-6) which is a major determinant of CRP gene expression (Wellen, 2003; Nyandak, 2007; Schulz, 2011; Basir, 2012). An increase in inflammatory conditions cause increased hs-CRP protein in the liver. The effect of that increases estrogen levels during the luteal phase which triggers an increase in prostaglandins and causes an inflammatory response.The purpose of this research is to know the difference in the levels of hs-CRP according to Body Mass Index and the degree of premenstrual syndrome.This research is a quantitative research with the kind of analytical research studies. The design of the research was cross sectional study. The study was conducted at the Padang Health Ministry Polytechnic. The population in this study were all fertile women aged 18-24 years who were active in studying at the Padang Health Ministry Polytechnic. The sample of this research were all populations that met the inclusion and exclusion criteria.The results of the research showed a mean difference where the levels of hs-CRP were higher in obese adolescents compared to normal BMI and it also showed a mean difference where the levels of hs-CRP were higher in moderate PMS degrees compared to low PMS degrees with p <0.05.There is a significant relationship between the Body Mass Index and the degree of premenstrual syndrome. It is necessary to have a weight loss program in people with obesity and weight control to keep it in ideal condition, so that it can reduce the increase in complaints on premenstrual syndrome.